Integrating Geology and Hydrogeology for Sustainable Environmental Management : A Review - Dr. Ghanshyam Shakar (International Journal of Scientific Research in Science and Technology, 2024)
The combination of geology and hydrogeology as a basis for environmentally sustainable management is reviewed in this paper. In order to handle issues like water scarcity, contamination, and ecosystem preservation, the interaction between geological formations and groundwater systems is essential. The study looks at important topics such groundwater recharge dynamics, aquifer characterization, and how geological formations affect water flow. Developments in numerical modeling, remote sensing, and geophysical methods are emphasized as crucial instruments for precise management and assessment. Examples from real-world situations show how integrated strategies can help address problems including pollution, over extraction, and land subsidence. Interdisciplinary research is crucial for filling in knowledge gaps and encouraging the sustainable use of groundwater resources, according to the review. The study also emphasizes how important it is to integrate geoscientific knowledge into policy frameworks in order to promote environmentally responsible practices and robust water systems. This synthesis offers a road map for utilizing hydrogeology and geology to achieve environmental sustainability over the long run.